Questioning the word. Oral communication and learning in the Universidad Nacional de Córdoba (Praxis Educativa, 2019)
Centered on oral communication in the Academy, the paper sets a dialogue between two voices: on the one hand, the practises and concerns of the students of a workshop on communicational abilities offered in the National University of Cordoba in 2018; and, on the other hand, contributions from language sciences (Barthes, 2003; Todorov, 2008; Van Dijk, 1983) and philosophy (Foucault, 1996; Skliar, 2015).Which are the challenges on oral academic communication for those who teach and learn? How do students learn when teachers give their lessons and how do they take the word in order to say their knowledge? From those starting points and in a flexible essay, the papertext unfolds reflections on philosophical, psychological, and socio-anthropological concepts --social control, power and self-care - as well as representations of technical concepts —conceptual precision, the adjustment to the communication situation, the discipline lexical realm, and the macro-structure —in order to consider some social and didactic implications of oral communication in the university environment.
Keywords: academic discourse; university; education; oral communication; conversation